The Eruption of Submarine Rhyolite Lavas and Domes in the Deep Ocean – Havre 2012, Kermadec Arc - Ikegami, Fumihiko; McPhie, Jocelyn; Carey, Rebecca; Mundana, Rhiannan; Soule, Adam; Jutzeler, Martin (Frontiers in Earth Science, 2018)
Silicic effusive eruptions in deep submarine environments have not yet been directly observed and very few modern submarine silicic lavas and domes have been described. The eruption of Havre caldera volcano in the Kermadec arc in 2012 provided an outstanding database for research on deep submarine silicic effusive eruptions because it produced 15 rhyolite (70–72 wt.% SiO2) lavas and domes with a total volume of ∼0.21 km3 from 14 separate seafloor vents. Moreover, in 2015, the seafloor products were observed, mapped and sampled in exceptional detail (1-m resolution) using AUV Sentry and ROV Jason2 deployed from R/V Roger Revelle. Vent positions are strongly aligned, defining NW-SE and E-W trends along the southwestern and southern Havre caldera margin, respectively. The alignment of the vents suggests magma ascent along dykes which probably occupy faults related to the caldera margin. Four vents part way up the steeply sloping southwestern caldera wall at 1,200–1,300 m below sea level (bsl) and one on the caldera rim (1,060 m bsl) produced elongate lavas. On the steep caldera wall, the lavas consist of narrow tongues that have triangular cross-section shapes. Two of the narrow-tongue segments are connected to wide lobes on the flat caldera floor at ∼1,500 m bsl. The lavas are characterized by arcuate surface ridges oriented perpendicular to the propagation direction. Eight domes were erupted onto relatively flat sea floor from vents at ∼1,000 m bsl along the southern and southwestern caldera rim. They are characterized by steep margins and gently convex-up upper surfaces. With one exception, the domes have narrow spines and deep clefts above the inferred vent positions. One dome has a relatively smooth upper surface. The lavas and domes all consist of combinations of coherent rhyolite and monomictic rhyolite breccia. Despite eruption from deep-water vents (most >900 m bsl), the Havre 2012 rhyolite lavas and domes are very similar to subaerial rhyolite lavas and domes in terms of dimensions, volumes, aspect ratio, textures and morphology. They show that lava morphology was strongly controlled by the pre-existing seafloor topography: domes and wide lobes formed where the rhyolite was emplaced onto flat sea floor, whereas narrow tongues formed where the rhyolite was emplaced on the steep slopes of the caldera wall.